Experimentální příprava korozivních preparátů orgánů velkého zvířete - Pálek, R; Liška, V; Eberlová, L; Mírka, H; Svoboda, M; Haviar, S; Emingr, M; Brzoň, O; Mik, P; Třeška, V (Rozhledy v chirurgii, 2018)
INTRODUCTION: Corrosion casts (CCs) are used for the visualization and assessment of hollow structures. CCs with filled capillaries enable (with the help of imaging methods) to obtain data for mathematical organ perfusion modelling. As the processing is more difficult in case of organs with greater volume of the vasculature, mainly organs from small animals have been cast up to now. The aim of this study was to optimize the protocol of corrosion casting of different organs of pig. Porcine organs are relatively easily accessible and frequently used in experimental medicine. METHOD: Organs from 10 healthy Prestice Black-Pied pigs (6 females, body weight 35-45 kg), were used in this study (liver, spleen, kidneys and small intestine). The organs were dissected, heparin was administered into the systemic circulation and then the vascular bed of the organs was flushed with heparinized saline either in situ (liver) or after their removal (spleen, kidney, small intestine). All handling was done under the water surface to prevent air embolization. The next step was an intraarterial (in case of the liver also intraportal) administration of Biodur E20® (Heidelberg, Germany) resin. After hardening of the resin the organ tissue was dissolved by 15% KOH and the specimen was rinsed with tap water. Voluminous casts were stored in 70% denatured alcohol, the smaller ones were lyophilized. The casts were assessed with a stereomicroscope, computed and microcomputed tomography (CT and microCT), a scanning electron microscope (SEM) and high-resolution digital microscope (HRDM). RESULTS: High-quality CCs of the porcine liver, kidneys, spleen and small intestine were created owing to the sophisticated organ harvesting, the suitable resin and casting procedure. Macroscopic clarity was improved thanks to the possibility of resin dying. Scanning by CT was performed and showed to be a suitable method for the liver cast examination. MicroCT, SEM and HRDM produced images of the most detailed structures of vascular bed. Despite the fact that SEM seems to be an irreplaceable method for CCs quality control, it seems that this modality could be partly replaced by HRDM. MicroCT enabled to obtain data about three-dimensional layout of the vascular bed and data for mathematical modelling of organ perfusion. With regard to the quality of the CCs, they could also be used to teach human anatomy. CONCLUSIONS: The protocol of the corrosion casting of the porcine liver, kidneys, spleen and small intestine CCs was optimized. Thanks to different imaging methods, the CCs can be used as a source of data on three-dimensional architecture of the vascular bed. These data can be used for mathematical modeling of organ perfusion which can be helpful for example for optimization of organ resections.Key words: corrosion casts microvasculature Biodur E20® domestic pig animal model.
Keywords: Corrosion; X-Ray Microtomography; rentgenová mikrotomografie; korozní odlévání; Animals; lidé; Female; ženské pohlaví; mikroskopie elektronová rastrovací; Microscopy, Electron, Scanning; Corrosion Casting; Humans; zvířata; Animal Structures; anatomické struktury zvířat; koroze